2022
DOI: 10.9734/ijecc/2022/v12i1131022
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Electric, Magnetic and Bio Film on the Growth, Yield and Yield Attributing Traits of Radish (Raphanus sativus L.)

Abstract: The present study was carried out for Influence on electric, magnetic and Bio - film in the growth, yield, and yield attributing traits of radish (Raphanus sativus L.) was made to identify the effect of seed priming of different kinds on seed quality characters of radish and to find out suitable seed priming method for radish. For this purpose, 13 priming treatments were taken in Randomized Block Design including control on radish seed was studied under field conditions during Rabi, 2020-21. Analysis of varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Along from that, adding compost and compost tea to vermicompost tea helps to fix atmospheric nitrogen and excrete certain growth stimulants (Saharan and Nehra, 2011). Similar findings were found by (Reddy and Reddy 2005;Pant et al ,2011;Kaswan et al, 2013;Shedeed et al, 2014;Singh and Ram 2014;Singh et al, 2015;Monira et al, 2019). Across all organic fertilizer treatments, number of leaves per plant were increased significantly as compared with the control.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Along from that, adding compost and compost tea to vermicompost tea helps to fix atmospheric nitrogen and excrete certain growth stimulants (Saharan and Nehra, 2011). Similar findings were found by (Reddy and Reddy 2005;Pant et al ,2011;Kaswan et al, 2013;Shedeed et al, 2014;Singh and Ram 2014;Singh et al, 2015;Monira et al, 2019). Across all organic fertilizer treatments, number of leaves per plant were increased significantly as compared with the control.…”
Section: Discussionsupporting
confidence: 85%
“…As a result, enhanced nutrient availability, improved soil physical characteristics, and increased activity of microorganisms with greater amounts of organics may have aided in raising plant height, number of leaves, leaf area, and leaf area index. (Reddy and Reddy, 2005). The analysis of this study showed that average bulb weight and total bulb yield were significantly influenced by the effect organic fertilizer treatments (P < 0.05).…”
Section: Discussionmentioning
confidence: 64%